Solid‐phase extraction of drugs with cuttlefish bone powder as a sorbent. Issue 18 (26th August 2018) - Khazri, Hassen; Ghorbel‐Abid, Ibtissem; Debrauwer, Laurent; Kalfat, Rafik; Trabelsi‐Ayadi, Malika
Abstract: We investigated cuttlefish bone powder for the solid‐phase extraction of naproxen, ibuprofen, and carbamazepine. The basic principles controlling the extraction are presented to aid in the choice of the nature and quantity of the extracting phase according to the sample matrix and the solute properties, based on the mechanisms of phase retention. Their retention mechanism is based on hydrogen bonding and electrostatic interactions. The results show a significant recovery rate for the three drugs, selectivity, and low cost. The method has successfully reduced the amount of tested pharmaceuticals with recoveries >87% at pH 4.